Profile of the socio-economic status of students in Notre Dame of Jaro, Leyte - Borgonia, Marissa Leticia T. (Animo Repository, 1985)
This study seeks to determine the socio-economic profile of the high school students of the Notre Dame of Jaro, Leyte in the school year 1984-1985.The descriptive survey method of research was used to determine the socio-economic status of the students. A total of 167 high school students were the respondents of this study. The questionnaire used and modified by the researcher was adapted from the PAASCU socio-economic survey used by Dalwatan (1979). The factors considered in the students' questionnaire were divided into two parts: information about the students and information about the family of the respondents. To determine their socio-economic status, the information included the following: occupation, family income, educational attainment, property, social position and type of residence.On the basis of the findings of the study, it can be concluded that almost all parents of the respondents were literate except 1 percent who had no schooling at all. Majority of them acquired elementary and secondary education. Majority of the heads of the families engaged in subordinate services. The main source of income was farming. Aside from the main source of income, the families of the respondents have sari-sari stores and other members of the family were fish vendors. Most of the families of the respondents owned the land where their houses were built.Based on the findings on the SES of the NDJ students, Notre Dame of Jaro catered to students coming from the lower-middle SES income group.